Artikulasi dan Revitalisasi Kultur-Natur Masyarakat Adat (Kajian atas Resilensi Masyarakat Adat saat Pandemi di Dataran Tinggi Kabupaten Gowa - Imamul Haq; Ibrahim; Surahmat Tiro (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
This field research seeks to show the effects of the crisis as a direct impact of the pandemic on indigenous communities in rural areas. Using an ethnographic approach, as well as a methodology in anthropological research, which emphasizes the research’s direct experience in understanding the socio-cultural dynamics of the subject being studied. This study acknowledges that the process of adaptation by the community in overcoming the crisis, is made possible by the availability of various methods of agricultural commodity production: vegetables-holtikultur and rice. The last option is to sell surplus rice production, whereas for small farmers, rice is a subsistence crop (private consumption). More than, indigenous peoples not only adapt but are also able to innovate by create a central laboratory for herbal plants, which in fact has long been the local knowledge of the shaman-medicine (sanro/balian). This activity is referred to in this study as a form of resilience by revitalizing their culture and nature. Interestingly, this resilience is practiced by young aktivist through the return home movement and encourages local knowledge-based practices that are revitalized as part of the articulation of the indigenous peoples' struggle for recognition of their identity, rights and livelihood (recognition politics) by the state. Keywords: Articulation, revitalization of culture dan nature, resilience, indigenous peoples, Pandemic Covid-19.